African higher education institutions catching up: The potential of 4IR in closing the digital deficits - Msila, Vuyisile (Technium Social Sciences Journal, 2023)
The new digital cultures brought by the Fourth Industrial Revolution (4IR) are forcing universities to transform their practices as they prepare students for a future that will magnify the use of digital tools. Throughout the world, institutions of higher learning are gearing to maximise the benefits that could be gained from the 4IR. The concept, engaged university, ensures that the uniiversities will not leave the communities around them behind as they prepare for the future, for universities will play a huge role in contributing to the progress in societies. This conceptual article examines the opportunities of 4IR in African institutions of higher learning. The 4IR has potential to solve many of the ills in Africa, for the African societies still suffer ill health, poverty and illiteracy. The promise of the 4IR brings hope of minimising these ills as Africa moves towards advancement. Furthermore, there has been much balkanisation in African education hence some believe that the 4IR can create links between institutions within states and the entire African continent. Not only will new technologies transform research, scholarship and teaching, but these would also have impact on bringing forth new epistemologies although there is still a battle for more resources. The major challenge for 4IR in Africa will be to create links between new technological cultures and African cultures; universities are well-placed to face such challenges.